Mixed methods instrument validation: Evaluation procedures for practitioners developed from the validation of the Swiss Instrument for Evaluating Interprofessional Collaboration - Jean Anthony Grand-Gui; Franziska Geese; Katja Uhlmann; Angela Blasimann; Felicitas L. Wagner; Florian B. Neubauer; Sören Huwendiek; Sabine Hahn; Kai-Uwe Schmitt (BMC, 2023)
Abstract Background Quantitative and qualitative procedures are necessary components of instrument development and assessment. However, validation studies conventionally emphasise quantitative assessments while neglecting qualitative procedures. Applying both methods in a mixed methods design provides additional insights into instrument quality and more rigorous validity evidence. Drawing from an extensive review of the methodological and applied validation literature on mixed methods, we showcase our use of mixed methods for validation which applied the quality criteria of congruence, convergence, and credibility on data collected with an instrument measuring interprofessional collaboration in the context of Swiss healthcare, named the Swiss Instrument for Evaluating Interprofessional Collaboration. Methods We employ a convergent parallel mixed methods design to analyse quantitative and qualitative questionnaire data. Data were collected from staff, supervisors, and patients of a university hospital and regional hospitals in the German and Italian speaking regions of Switzerland. We compare quantitative ratings and qualitative comments to evaluate the quality criteria of congruence, convergence, and credibility, which together form part of an instrument's construct validity evidence. Results Questionnaires from 435 staff, 133 supervisors, and 189 patients were collected. Analysis of congruence potentially provides explanations why respondents' comments are off topic. Convergence between quantitative ratings and qualitative comments can be interpreted as an indication of convergent validity. Credibility provides a summary evaluation of instrument quality. These quality criteria provide evidence that questions were understood as intended, provide construct validity, and also point to potential item quality issues. Conclusions Mixed methods provide alternative means of collecting construct validity evidence. Our suggested procedures can be easily applied on empirical data and allow the congruence, convergence, and credibility of questionnaire items to be evaluated. The described procedures provide an efficient means of enhancing the rigor of an instrument and can be used alone or in conjunction with traditional quantitative psychometric approaches.